The limits of transparency as a means of reducing corruption - Daniel Parra; Manuel Mu\~noz-Herrera; Luis Palacio (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
We use a laboratory experiment to study the impact of transparency on reducing corruption in contexts where embezzlement and bribery can co-occur. These contexts are closely related to grand corruption settings, where different types of corruption occur and allow people in power to take advantage of their position. Transparency is expected to have a positive effect on reducing corruption. However, our results show that transparency decreases embezzlement by roughly 10 percentage points, while it has no significant effect on bribery. The observed differential impact of transparency could be attributed to strategic lying by the resource manager, who acts as if low public investment rates were a consequence of bad luck (low budget) instead of misappropriation. This suggests that the impact of transparency cannot be generalized to all types of corruption when different types co-exist.
Keywords: C91; D72; D73; 330; embezzlement; bribery; grand corruption